Construction Of Hybrid Geometric Modelling For Injection Mould Using Cadcam System - Tan, Jian Xin (Universiti Sains Malaysia, 2019)
This project describes a procedure for automatic feature recognition to help in mould designing. Hybrid representation approach is used in automatic feature recognition to extract the geometric information of the feature in order to identify the undercut features. Boundary representation(B-rep) is applied in the shape representation by using the topology and geometry. The proposed approach that used the Face Adjacency Hypergraph describes the shape of the undercut features by representing the relationships among the faces of the features. The Face-to-Face Composition is applied to study the relationship between the main feature and undercut features. Part A, Part B and Part C were created and used the automatic feature recognition to classify the depression and protrusion feature. The algorithms based on the heuristic rule is used to determine the best parting line and parting direction of the parts by comparing their geometric information of the feature. These automatic feature recognition identified their shape of concave and convex feature according their depression or protrusion faces and their face adjacency relationship. These approaches are helpful in creating the core and cavity automatically. It will help to simplify the process of mould designing and reduce the time of moulding designing. Therefore, these approaches will have significant effect on increasing the productivity in manufacturing industry.